A comparison of digestive strategies for fishes with different feeding habits: Digestive enzyme activities, intestinal morphology, and gut microbiota - Jiao, Fang; Zhang, Lei; Limbu, Samwel Mchele; Yin, Hong; Xie, Yuqing; Yang, Zihan; Shang, Zongmin; Kong, Lingfu; Rong, Hua (Ecology and evolution, 2023)
Fish feeding habit determines the digestive tract structure and intestinal microflora. However, the relationship between feeding habit, digestive intestinal morphology, and microbial diversity of omnivorous, herbivorous, plankton feeder, and carnivorous fish from the same environment has not been compared. This study compared the digestive enzyme activities, intestinal morphology, and intestinal microflora of omnivorous (Carassius auratus), herbivorous (Ctenopharyngodon idellus), carnivorous (Siniperca chuatsi), and plankton feeder (Schizothorax grahami) fishes and predicted the potential functions of specific microflora on different nutrients. Twelve intestine samples were collected from each of the four fishes from Dianchi Lake. The composition and diversity of microbial communities were determined by using high‐throughput sequencing of 16S rDNA. The results showed that the carnivorous fish (S. chuatsi) had higher trypsin and pancrelipase activities in the hepatopancreas and enteropeptidase in the intestine, but lower amylase activities in the intestine. The carnivorous fish intestine had more microvilli branches and complex structures than other fish species in the order carnivorous > herbivorous > plankton feeder > omnivorous. The intestinal microflora diversity was higher in the omnivorous fish and followed the order omnivorous > herbivorous > plankton feeder > carnivorous. Acinetobacter species and Bacteroides species were the most dominant flora in the carnivorous and herbivorous fishes, respectively. Acinetobacter species and Pseudomonas species might help the host to digest protein, while Bacteroidetes species may help the host to digest cellulose. Taken together, feeding habit determines the digestive enzyme activities, intestinal tissue morphology, and differential colonization of fish intestinal flora. The knowledge obtained is useful in feed formulation and feeding practices for the studied fish species. Feeding habit determines the digestive tract structure and intestinal microflora. However, the relationship between feeding habit, digestive physiology intestinal, and microbial diversity of omnivorous, herbivorous, filter‐feeder, and carnivorous fish reared in the same pond has not been compared. This study compared the digestive enzyme activities, intestinal morphology, and intestinal microflora of omnivorous (Carassius auratus), herbivorous (Ctenopharyngodon idellus), carnivorous (Siniperca chuatsi), and filter‐feeder (Shizothorax grahami) and predicted the potential functions of specific microflora on different nutrients.